ANALISIS POTENSI PENGEMBANGAN PERTANIAN ORGANIK DALAM UPAYA PENINGKATAN PENDAPATAN PETANI (Studi Kasus Pertanian Rakyat di Kecamatan Maro Sebo Kabupaten Muaro Jambi) - Siti Aminah (Universitas Batanghari, 2017)
Skyrocketing demand for organic agricultural products (without using chemicals), during these last few months because consumers are aware and selective top-qualityhealth products of agriculture. Agricultural product demand being high is vegetables, rice, fruit, spices, coffee and tea. Organic gardening tends to be more environmentally friendly because of the nature of the specific local. Ideally we strive to build plantations (at least the pilot orchards) organic. For the potential feasibility of agricultural development efforts on Agriculture organic food crops in Maro Sebo. To assess the feasibility of the venture with the pattern of organic farming tools used instruments namely Merchantibility Loss – Profit, Return Cost Ratio (R/C). Benefit Cost Ratio, The Break Event Point (BEP). The feasibility analysis of effort three commodities to agricultural businesses, namely rice, maize and chilli was able to provide considerable benefits for farmers. Keyword: organic farming, farmers' income